2016
DOI: 10.1021/acsnano.6b04143
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Dosing of Fumed Silica Leads to Profibrogenic Effects through Unique Structure–Activity Relationships and Biopersistence in the Lung

Abstract: Contrary to the notion that the use of fumed silica in consumer products can “generally (be) regarded as safe” (GRAS), the high surface reactivity of pyrogenic silica differs from other forms of synthetic amorphous silica (SAS), including the capacity to induce acute membrane damage and acute pro-inflammatory changes in the murine lung. In addition, the chain-like structure and reactive surface silanols also allow fumed silica to activate the NLRP3 inflammasome, leading to IL-1β production. This pathway is kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

7
2

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 52 publications
(146 reference statements)
0
53
0
Order By: Relevance
“…70 Single bolus dose instillation of 21 mg/kg fumed silica did not induce sustained IL-1β production or sub-chronic pulmonary effects, due to the comparatively high rate of dissolution and clearance of fumed silica from the lung. In contrast, repetitive dosing could lead to biopersistence with a change in lung toxicity, and the NLRP3 inflammasome pathway was continuously activated by repetitive dose administration of 3 × 7 mg/kg fumed silica, one week apart.…”
Section: Surface Silanol Density Determines Fumed Silica Induced Plasmentioning
confidence: 86%
“…70 Single bolus dose instillation of 21 mg/kg fumed silica did not induce sustained IL-1β production or sub-chronic pulmonary effects, due to the comparatively high rate of dissolution and clearance of fumed silica from the lung. In contrast, repetitive dosing could lead to biopersistence with a change in lung toxicity, and the NLRP3 inflammasome pathway was continuously activated by repetitive dose administration of 3 × 7 mg/kg fumed silica, one week apart.…”
Section: Surface Silanol Density Determines Fumed Silica Induced Plasmentioning
confidence: 86%
“…71 It is also important to consider that the release of arsenic from III-V arsenides at chronic low exposures might induce lung cancer. 14, 71 In spite of using what may currently constitute an unrealistic high-dose in our studies, it is important to be aware of dosimetry considerations when assessing exposures to III-V particulates in the semiconductor industry, particularly in the maintenance areas. Successful technology has been implemented to assess the airborne spread of nanoparticles contained in the primary CMP slurries.…”
Section: Discussionmentioning
confidence: 99%
“…Although these findings have improved our understanding with respect to the correlation between Si-NPs physicochemical characteristics and their toxicity, further in vivo analyses are needed to facilitate their application in translational nanomedicine. A finding by Sun et al 29 indicated that although a single high-dose exposure of fumed Si-NPs to pulmonary system did not induce a profibrogenic effect, repetitive exposure at a lower dose led to a significant subchronic inflammatory response in the murine lungs. Though this study was focused on pulmonary toxicity of fumed silica, repetitive administration of colloidal Si-NPs might show similar pro-inflammatory effects in the long-term.…”
Section: Colloidal Solid Si-npsmentioning
confidence: 99%